The influence of high-intensity interval training on anthropometric variables of adults with overweight or obesity: a systematic review and network meta-analysis - Andreato L.V.* (2019)
© 2018 World Obesity Federation Objective: The goal of this study was to evaluate the influence of high-intensity interval training (HIIT) on anthropometric variables in adults afflicted with overweight or obesity and to compare the effects with those of moderate-intensity continuous training. Methods: A computer literature search was performed for HIIT intervention studies that evaluated anthropometric variables in adults afflicted with overweight or obesity. Results: Of the 857 articles retrieved in the electronic search, 48 met the inclusion criteria. The analyses demonstrated that HIIT was effective in decreasing body mass (−1.45 kg [95% CI: −1.85 to −1.05 kg]), body mass index (−0.44 kg m −2 [95% CI: −0.59 to −0.30 kg m −2 ]), waist circumference (−2.3 cm [95% CI: −3.1 to −1.4 cm]), waist/hip ratio (−0.01 [95% CI: −0.02 to −0.00]), body fat percentage (−1.29% [95% CI: −1.70% to −0.87%]) and abdominal visceral fat area (−6.83 cm 2 [95% CI: −11.95 to −1.71 cm 2 ]). When considering equalization between the two methods (energy expenditure or workload matched), no differences were found in any measure except body mass (for which HIIT was superior). Conclusions: High-intensity interval training and moderate-intensity continuous training results were similar, particularly when equalization between the two methods was considered. Thus, HIIT can be used as a secondary method for the treatment of obesity in adults.